2011
DOI: 10.1186/1471-2148-11-49
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Asian diversity: first insights into the complex mtDNA structure of Laos

Abstract: BackgroundVast migrations and subsequent assimilation processes have shaped the genetic composition of Southeast Asia, an area of close contact between several major ethnic groups. To better characterize the genetic variation of this region, we analyzed the entire mtDNA control region of 214 unrelated donors from Laos according to highest forensic quality standards. To detail the phylogeny, we inspected selected SNPs from the mtDNA coding region. For a posteriori data quality control, quasi-median network cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 36 publications
3
48
1
4
Order By: Relevance
“…It also suggest that China, near Tibet, as a possible origin, from there they entered Myanmar around the 6th-7th century AD, where they still live in large number. Some group might be then migrated to Bangladesh and Thailand [25].…”
Section: Discussionmentioning
confidence: 99%
“…It also suggest that China, near Tibet, as a possible origin, from there they entered Myanmar around the 6th-7th century AD, where they still live in large number. Some group might be then migrated to Bangladesh and Thailand [25].…”
Section: Discussionmentioning
confidence: 99%
“…The number of intrapopulation MPD were 7.5657 (Isan-Ub), 7.8086 (Isan-Bu), and 7.2660 (Isan-Ch), reflected higher genetic heterogeneity within Isan-Bu than Isan-Ub and Isan-Ch. The interpopulation MPD, ranged from 7.6749 to 7.9394, were relatively high compared to previous report (Bodner et al, 2011) reflecting genetic differentiation among them. Genetic structure among the populations was tested for significant variation by AMOVA (Excoffier et al, 1992).…”
Section: Genetic Variation and Population Expansion Of The Studied Thmentioning
confidence: 47%
“…Because of an extensively ethnic diversity as described in Bodner et al (2011), the contribution from parental Lao in LPRD to the admixed Thai-Isan populations might not be purely from the Tai-Kadai speaking Lao, but the MonKhmer and Hmong-Mien Laos could also be the sources.…”
Section: Genetic Admixturementioning
confidence: 99%
See 1 more Smart Citation
“…The HVR-1 π i in Hmong, Lao Song, and Thai-Siam populations was 0.02365, 0.02112, and 0.02110, respectively. Several studies on several populations in Thailand reported the range of the HVR-1 H d , which varied from 0.931 to 1.000, and that of π i varied from 0.0169 to 0.0235 (Fucharoen et al, 2001;Lertrit et al, 2008;Bodner et al, 2011;Boonsoda et al, 2013;Kutanan et al, 2014). These values indicated that the genetic diversity of the three ethnic populations in this study were relatively high.…”
Section: Haplotype Analysismentioning
confidence: 49%